EGS 地熱發電相關法制與檢討及其成本分析探討(Ｉ) - 戴秀雄;徐光蓉 (2013)
再生能源在發展上，面對最大困難之一便是其不穩定性，其中又以普及的太陽能 與風能為最。因而尋求穩定且能充作基載的再生能源，便成為各國最重要當前再生能 源發展課題。地熱能之運用無疑正符合這種穩定供應特性之再生能源，然而淺層地熱 之利用強烈依賴地質條件，並非隨手可得者，因此例來僅為少數地熱發達國家(如冰島) 所慣常使用。這一點隨著深層地熱技術之發展而獲得改變，而此中最重要者莫過於EGS 技術，致德、美等國近年來紛紛轉向發展深層地熱發電技術，以做為未來再生能源之 主流。 我國迄今在地熱發電方面之經驗相當欠缺，一方面實驗經驗較少，另一方面更無 商業運轉之前例，更遑論深層地熱技術的推動；故今欲推動EGS 實驗，勢必碰觸過去 所未面臨之新問題，其中特別引發疑慮者即在於法律面之顧慮，以及經濟成本上資訊 之未知性。 本研究乃對EGS 及地熱發電實驗在我國所面臨的法律課題與經濟成本問題進行研 究，並提供其他地熱實驗計畫法規爭議上之協助，期能提前發現相關法規上前在困境， 並提出解決之建議，同時再提供貼近實務之經濟成本計算模型。 As a stable energy resource the geothermal become one of the favorites renewable energy. But the surface close geothermal depends strongly on geological condition o f sites. Therefore the using of surface close geothermal becomes privilege of some countries, which benefits from special geological structure, like Iceland. This situation has been changed since the developing of deep geothermal technology, especially EGS. Germany and USA have since then invested more in deep geothermal technology and expect its growth as mainstream energy resource in future. Except for Cing-Shueh experimental geothermal plant, neither surface close nor deep geothermal technology was well known in Taiwan. For this reason it will be expected, that the experiments of EGS, and also surface close geothermal experiments, will forced to face to some till now unknown problems, especially by legal and economic issues in Taiwan. This study will collect the information which generated by EGS and other geothermal experiments and the information about geothermal from USA, Germany, Iceland and Japan in order to find out the potential legal problems and the cost analytic model, which fits Taiwan’s situation. This study will also work as support team for other geothermal experiments projects by dealing with legal problems.